Potensi Likuifaksi Di Kabupaten Konawe Utara Sulawesi Tenggara Berdasarkan Metode Susceptibility Rating Factors (SRF) - Cendra Jaya, Rio Irhan Mais; Deniyatno (OPHIOLITE: Jurnal Geologi Terapan, 2024)
The liquefaction disaster that occurred in Palu, Central Sulawesi, was caused by a 7.5 SR. The movement of the Palu-Koro Fault triggered the earthquake which was then followed by liquefaction. North Konawe Regency, Southeast Sulawesi, is crossed by the Lawanopo Fault which is a continuation of the Palu-Koro Fault, so that North Konawe Regency has the potential for liquefaction. BMKG seismic data records that >90% of earthquake events in North Konawe are triggered by movements of the Lawanopo Fault. This research focuses on the potential for liquefaction that can be triggered by earthquake activity in North Konawe Regency. Susceptibility Rating Factor (SRF) method is used by calculating the liquefaction susceptibility index (ISL) based on historical parameters, geological data, soil texture and composition, and hydrogeological data. North Konawe Regency has 5% areas with high liquefaction potential, 2% medium potential, 6% low potential, and 87% very low potential. Areas with high potential (5%) and medium potential (2%) are densely populated areas because they are located in the center of the capital city of North Konawe Regency. This area is a basin formed due to the activity of the Lawanopo Fault.